Paleomagnetism and Cyclostratigraphy of the Middle Ordovician Krivolutsky Suite, Krivaya Luka Section, Southern Siberian Platform: Record of Non-Synchronous NRM-Components or a Non-Axial Geomagnetic Field? - Rodionov, V.P; Dekkers, M.J; Khramov, A.N; Gurevich, E.L; Krijgsman, W; Duermeijer, C.E; Heslop, D
a1_The Middle Ordovician Volginsky and Kirensky fossil zones were sampled in the Krivaya Luka section (Krivolutsky suite) that outcrops along the Lena river in Siberia. The Volginsky and Kirensky zones are coeval to the Llandeilo in the global geologic time scale. The Krivaya Luka section consists of siltstones, clays, sandstones, and limestones, and displays a remarkably distinct sedimentary cyclicity, especially in its reddish middle part. Stepwise thermal demagnetization yields three NRM components. Component A, isolated in the 100—250°C interval can be either normal or reversed. The normal A-component has a direction close to recent local magnetic field. The reversed A-component directions are scattered around a direction close to that of the lower Triassic Siberian traps. Component B has unblocking temperatures that range from 400 to 500°C and is represented mainly by normal polarity directions. The B-component, isolated from rocks of the middle part of the section is of a normal polarity with D = 176.5°, I = 30.0° and a North pole position at 16.2°S, 111.3°E. The other parts of the section are characterized by intermediate B-directions, which resulted possibly by partially overlapping A- and C-components. The highest temperature dual-polarity component C was isolated in the 550—670°C interval, resulting in the detection of two complete polarity zones and three magnetic reversals. The C-component is characterized by the following mean directions: for the reversed component D = 335.7°, I = 6.9°, and for the normal component D = 188.6°, I = 28.0°, which is very close to the normal polarity directions of the B-component. a2_The corresponding paleomagnetic North pole for reversed polarity rocks is 32.6°S, 137°E, which is typical of Middle Ordovician rocks from Siberia - the mean pole for Llanvirn-Llandeilo is 30°S, 136°E (cf. Smethurst et al., 1998) - whereas for normal polarity rocks the pole position 17.2°S, 99.1°E is markedly different. Nevertheless, we assume that the C-component records the ancient ...